Aligning macroeconomic policies for agricultural transformation in Africa - Mukasa, Adamon N.; Ndung’u, Njuguna; Shimeles, Abebe (International Food Policy Research Institute, 2020)
This chapter discusses how accounting for macroeconomic perspectives when establishing agricultural policies can help African governments ensure that their agricultural sectors become productive, competitive, and lucrative across agricultural value chains. It presents the two-way linkages between agricultureled growth strategies and macroeconomic policies by focusing on price, fiscal, monetary, exchange rate, and trade policies. It also discusses the main constraints to effective agricultural policy and the options for integrating agricultural perspectives when developing macroeconomic policies.